PENGEMBANGAN BAHAN AJAR BEBASIN (BELAJAR BERSAMA SEJARAH INDONESIA) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS - Shinta Sintia Kurniasari; Yoyo Zakaria Ansori; Yuyu Yuliati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Technological developments occur in various sectors, including education. Teachers are expected to utilize existing technology to enhance 21st-century skills, one of which is critical thinking. Based on the results of interviews conducted at four schools in Panyingkiran District, the learning process in the classroom has not fully utilized technology. Teachers still use outdated methods and rely on textbooks provided by the government, which results in students having low critical thinking skills. This study aims to develop teaching materials that can improve critical thinking skills of students. This study uses a 4D research model with four stages: Define, Design, Develop and Disseminate. The results of the validation test obtained a very valid category. Furthermore, based on the results of the assessment by teachers and students, this teaching material is very practical to use in the learning process. Meanwhile, the results of student tests on the developed teaching materials indicate the effectiveness of the use of BEBASIN teaching materials. Therefore, it can be concluded that this BEBASIN teaching material is suitable for use in learning social sciences content of the history of kingdoms in Indonesia.